Interactive periodic table in Scratch: A mathematical approach to periodic properties in chemistry teaching - Strieder , Rosangela Lucia; Souza , Marcela Zoratti de; Carvalho , José Wilson Pires; Negreiros , Cláudia Landin (Seven Editora, 2023)
The present work, “Interactive Periodic Table in Scratch: a mathematical approach to periodic properties in chemistry teaching” argues that it is no longer possible to separate education from the environment in which the student is inserted, that is, it is increasingly necessary to use of technological resources in teaching. However, it is important to emphasize that the use of technological resources needs to involve the student, showing him that technology is a resource that can enable the understanding of interrelated concepts of Chemistry and Mathematics, avoiding the simple memorization of concepts. In this context, the objective of the study was to discuss the contributions of using Scratch software in teaching science in the 9th grade of Elementary School through the construction of the interactive periodic table and interrelated concepts of Chemistry and Mathematics, seeking to provide students with the use of Scratch software theoretical and practical concepts to become fluent in digital technology and build an interactive periodic table. DOI:https://doi.org/10.56238/alookdevelopv1-165